2017
DOI: 10.1016/j.jcf.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Worsening anxiety and depression after initiation of lumacaftor/ivacaftor combination therapy in adolescent females with cystic fibrosis

Abstract: In both phase III studies of LUM/IVA, as well as an extension study, worsening of mental health was not reported as a common side effect. Here we describe five cases in adolescent female patients that suggest a worsening of anxiety or depression associated with its use. In these five patients, two experienced suicidal ideation and three made suicide attempts that resulted in psychiatric hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 5 publications
1
35
0
Order By: Relevance
“…Fourteen (26%) of the observational studies focused on patients with severe airflow obstruction, defined as ppFEV 1 < 40%; in 11 of these studies, patients accessed the CFTR modulator via a compassionate access program (also referred to as a "managed access", "early access', "expanded access", or "named patient" program) through the manufacturer [25,26,[29][30][31][32][33][34][35][36][37][38][39][40]. Twenty (65%) of the full manuscripts were deemed to have safety as a primary focus or outcome [27][28][29][30]32,33,[41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen (26%) of the observational studies focused on patients with severe airflow obstruction, defined as ppFEV 1 < 40%; in 11 of these studies, patients accessed the CFTR modulator via a compassionate access program (also referred to as a "managed access", "early access', "expanded access", or "named patient" program) through the manufacturer [25,26,[29][30][31][32][33][34][35][36][37][38][39][40]. Twenty (65%) of the full manuscripts were deemed to have safety as a primary focus or outcome [27][28][29][30]32,33,[41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…One large prospective cohort study reported four individuals (0.5% of the study cohort) discontinued LUM/IVA due to depression [42], and one individual in each of two smaller retrospective cohorts reported anxiety as the cause of discontinuation (4 and 5% of the respective cohorts) [45,75]. One case series described five adolescent females, comprising 24% of the adolescent females who initiated LUM/IVA at the reporting center, with new or worsening depression as early as two weeks following LUM/IVA initiation [47]. Two of the patients had suicidal ideation (one each with baseline and new-onset depression), while three of the patients had an attempted suicide requiring hospitalization (one with baseline and two with new-onset depression) [47].…”
Section: Lumacaftor/ivacaftor (Lum/iva)mentioning
confidence: 99%
“…Variation in clinician practice may be one factor, possibly driven by clinician belief in therapeutic efficacy, as magnitude of lung function improvement in LUM-IVA treated patients was approximately 1/3 of that seen in ivacaftor clinical trials. In addition, reports of increased side effects, both in clinical trials and in post-approval observations, may have led some clinician hesitation in initiation of therapy [2,9]. We also found that patients on government-sponsored health insurance plans were less likely than privately insured patients to receive LUM-IVA therapy after approval.…”
Section: Discussionmentioning
confidence: 67%
“…The incidence of drug discontinuation due to side effects was higher in females and in the group where individuals had an FEV1% predicted of 40% or less prior to initiation of therapy. Lumacaftor/ivacaftor may also be associated with worsening mental health issues such as worsening anxiety and suicidal ideation in females [15], and acute drops in FEV 1 (mean absolute decrease of approximately 10% after the first dose) mainly through bronchoconstriction was also reported [16]. Clinical experience in patients with ppFEV1 <40 is limited, and additional monitoring of these patients is recommended during initiation of therapy.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%